2022
DOI: 10.1155/2022/7768160
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrians Crossing and Walking Speeds Analysis in Urban Areas under the Influence of Rain and Personality Characteristics

Abstract: Pedestrians’ behavior plays an important role in designing pedestrian facilities, especially in urban areas. One of these behavioral characteristics is their moving speed on sidewalks, pedestrian streets, crosswalks at signalized intersections, and midblock crosswalks. The moving speed is strongly affected by personality traits such as age, weight, gender as well as environmental and geometric conditions. In this regard, the moving speed of 14,490 pedestrians was measured in urban area pedestrian-related facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The width of this range was directly related to the number of available data. According to previous research found in literature [ 16 ], through the Student’s t -Test it was possible to perform a test of statistical hypotheses in order to analyse any correlations between different categories within the same variable. The test was used to determinate whether the average values and the standard deviation of two datasets were significantly different from each other.…”
Section: Methodsmentioning
confidence: 99%
“…The width of this range was directly related to the number of available data. According to previous research found in literature [ 16 ], through the Student’s t -Test it was possible to perform a test of statistical hypotheses in order to analyse any correlations between different categories within the same variable. The test was used to determinate whether the average values and the standard deviation of two datasets were significantly different from each other.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence suggests that adverse weather conditions, such as the presence of rain, are associated with a higher likelihood and severity of pedestrian injury in crashes, as jaywalking might be more prevalent [61] and in general pedestrians might exhibit riskier and less compliant crossing behaviour [62]. The presence of rain has also been found to impact pedestrians' walking speed [63,64]. There is some indication that pedestrians' speed can be higher at dusk as a "walk-quickly" strategy might be adopted [65].…”
Section: Weather and Visibilitymentioning
confidence: 99%
“…e Kolmogorov-Smirnov test is utilized to recognize the normality of samples [23]. e comparison of the result of the K-S test called sig.…”
Section: Kolmogorov-smirnov (K-s) Testmentioning
confidence: 99%